EXTH-22. NEOADJUVANT IMMUNOTHERAPY WITH ANTI-PD1 ALTERS THE TUMOR MICROENVIRONMENT POST SURGERY IN A MODEL OF RECURRENT GLIOBLASTOMA. (12th November 2021) - Hoang-Minh, Lan; Doonan, Bently; von Roemeling, Christina; Yang, Changlin; Shin, David; Trivedi, Vrunda; Karachi, Aida; Wang, Yu; Mitchell, Duane
Abstract: SIGNIFICANCE: New promising clinical trials for glioblastoma are evaluating the efficacy of neoadjuvant immunotherapy in the context of recurrent tumor surgery. OBJECTIVE: We investigated the effects of neoadjuvant PD1 blockade on the glioma tumor microenvironment in a clinically relevant murine model of recurrent tumor. RESULTS: Using an orthotopic mouse KR158 resection model of glioblastoma that we have established, we show that neoadjuvant anti-PD1 and surgery enhance animal survival and increase the recruitment of CD8+ and CD4+ T cells at recurrent tumor sites following bulk tumor resection compared to surgery followed by adjuvant immunotherapy. Transcriptome and spatial genomic analyses reveal alterations in immune exhaustion and activation pathway signaling after neoadjuvant anti-PD1treatment when compared with adjuvant anti-PD1-treatment or surgery alone. CONCLUSIONS: These results provide insights into the effects of neoadjuvant PD1 blockade on the tumor microenvironment and uncover additional treatment targets.